Correlation between learning style, gender, and university location toward environmental problem-solving skills - Sari, Rima Meilita; Ridhwan, Ridhwan; Sahudra, Tengku Muhammad; Urfan, Faiz (International Journal of Evaluation and Research in Education (IJERE), 2025)
Environmental degradation in technological development is accelerating. Therefore, it requires environmental problem-solving skills. This study is aimed to determine university students’ learning style and skill to solve environmental problems based on gender and university location. In addition, this study also aims to find the correlation between learning styles, gender, and university location towards environmental problem-solving skills. The population of this study was the university student in Indonesia. This study employed a descriptive and correlational study. The researchers used the VARK test to find out the learning style. Meanwhile, the data on the environmental problem-solving skills collected by using a validated and tried out test instrument that refers to indicators from Ridhwan. The results of this study showed that the students’ learning styles tended to be visual at 50.49%. The environmental problem-solving skill was in the low category with an average score of 41.47. There was no any correlation between learning styles and gender with the ability to solve environmental problems, but in variable of university location, there was a significant correlation. This is because university differences are closely related to location differences and have an impact on access to learning facilities.